Amino functionalized zeolitic tetrazolate framework (ZTF) with high capacity for storage of carbon dioxide - Panda, Tamas; Pachfule, Pradip; Chen, Yifei; Jiang, Jianwen; Banerjee, Rahul (Chemical Communications, 2011)
A three dimensional -NH(2) functionalized Zeolitic Tetrazolate Framework (ZTF-1) has been reported. The framework adopts a dia topology (M-L-M angle is close to 156 degrees). ZTF-1 shows high CO(2) (273 K) and H(2) (77 K) uptake due to the presence of the free -NH(2) group and uncoordinated tetrazolate nitrogen.

Experimental and computational approach of understanding the gas adsorption in amino functionalized interpenetrated metal organic frameworks (MOFs) - Pachfule, Pradip; Chen, Yifei; Jiang, Jianwen; Banerjee, Rahul (Journal of Materials Chemistry, 2011)
Two isostructural, three dimensional, interpenetrated, amino (-NH2) functionalized Metal Organic Frameworks [Cd(ANIC)(2)] (Cd-ANIC-1) and [Co(ANIC)(2)] (Co-ANIC-1) with amine-lined pores have been reported. The framework adopts dia topology with interpenetration. Cd-ANIC-1 and Co-ANIC-1 show high CO2 (273 K) and H-2 (77 K) uptake due to the presence of free -NH2 groups and framework interpenetration. The effect of interpenetration and amino functionalization on gas uptake properties of MOFs has been analysed experimentally and computationally, in the isostructural MOFs Cd-ANIC-1 and Co-ANIC-1.

Structural isomerism and effect of fluorination on gas adsorption in copper-tetrazolate based metal organic frameworks - Pachfule, Pradip; Chen, Yifei; Sahoo, Subash Chandra; Jiang, Jianwen; Banerjee, Rahul (Chemistry of Materials, 2011)
Synthesis, structure, and gas adsorption properties of three Metal Organic Frameworks (MOFs) synthesized from predesigned ligands 4-(1H-tetrazole-5-yl)benzoic acid (4-TBA) and 2-fluoro-4-(1H-tetrazole-5-yl)benzoic acid (2F-4-TBA) along with Cu(II) as an metal precursor has been reported. Among these MOFs, Cu-9(4-TBA)(10)(C2H5OH)(2) (Cu-TBA-1) and Cu-2(4-TBA)(2)(DMF)(C2H5OH) (Cu-TBA-2) are structural isomers. Whereas, Cu-2(4-TBA)(2)(DMF)(C2H5OH) (Cu-TBA-2) and Cu-2(2-F-4-TBA)(2)(DMF)(2) (Cu-TBA-2F) have similar crystal structure. N-2 adsorption isotherms of the activated sample of Cu-TBA-1 and -2 exhibit types-I sorption behavior with a Langmuir and Brunauer-Emmett-Teller (BET) surface area of 686, 402 m(2)/g and 616, 356 m(2)/g, respectively. It is noteworthy that Cu-TBA-1 and -2 adsorbs 1.16 and, 1.54 wt % H-2, while Cu-TBA-2F adsorbs 0.67 wt % at 77 K and 1 atm. On the other hand, Cu-TBA-1 and -2 adsorb 3.08 and 2.54 mmol/g, while Cu-TBA-2F adsorbs 1.27 mmol/g of CO2 at 298 K and 1 bar pressure. H-2 adsorption sites in Cu-TBA-2 and -2F have been analyzed by molecular simulation.
Keywords: CO2 adsorption; fluorination; Hydrogen storage; Metal-organic framework; structural isomerism

Fluorinated metal-organic frameworks: advantageous for higher H-2 and CO2 adsorption or not? - Pachfule, Pradip; Chen, Yifei; Jiang, Jianwen; Banerjee, Rahul (Chemistry-A European Journal, 2012)
The synthesis, structure, and gas adsorption properties of three new metalorganic frameworks (MOFs) designed from isonicotinic acid (INA) and its fluorinated analogue 3-fluoroisonicotinic acid (FINA) along with CoII as the metal center have been reported. Co-INA-1 ([Co3(INA)4(O)(C2H5OH)3][NO3].C2H5OH.3?H2O; INA=isonicotinic acid) and Co-INA-2 ([Co(INA)2].DMF) are structural isomers as are Co-FINA-1 ([Co3(FINA)4(O)(C2H5OH)2].H2O; FINA=3-fluoroisonicotinic acid) and Co-FINA-2 ([Co(FINA)2].H2O), but the most important thing to note here is that Co-INA-1 and Co-FINA-1 are isostructural as are Co-INA-2 and Co-FINA-2. The effect of partial introduction of fluorine atoms into the framework on the gas uptake properties of MOFs having similar structures has been analyzed experimentally and computationally in isostructural MOFs.
Keywords: cobalt; fluorine; Hydrogen storage; metal-organic frameworks; microporous materials; X-ray diffraction

Enhancement of CO2 uptake in iso-reticular Co based zeolitic imidazolate frameworks via metal replacement - Panda, Tamas; Gupta, Krishna M.; Jiang, Jianwen; Banerjee, Rahul (CrystEngComm, 2014)
Three Co based Zeolitic Imidazolate Frameworks (Co-ZIF-68, -69 and -81) which adopt a GME topology with high porosity have been synthesized. These Co-ZIFs show high CO2 (273 K/298 K) uptake compared to their isostructural Zn based analogues, which has been proved experimentally as well as by ab initio calculations.